Coridone e il fuoco d’amore - Marco Fernandelli (Pallas, 2009)
It is generaly assumed that Virgil’ s second Bucolic was written first. Our analysis is no demonstration of the rightness of that thesis but picks out in the poem a few incipient tendencies that were to become manifest throughout Virgil’ s work, such as the art of using verse to mimetic ends, the symbolic value of the imagery and the ‘subjective’ mode of the narrative. Theocritus’ XI Idyll is the chief model of the second Bucolic. Virgil, however, diverges from it by attributing the unfortunate lover’s monologue not to a mythical figure like Polyphemus but to an ordinary shepherd, Corydon. The Latin poet operates the change by taking into account a secondary model, outside the bucolic genre, Meleagros’ 79 epigram (Gow – Page = AP XII 127). Studying the way Virgil draws inspiration from Meleagros’ text, structurally as well as thematically, throws also light on the genesis of an obviously new linguistic usage, ardeo as a transitive verb (v. 1 Formosum… ardebat Alexin) : that usage reflects, by condensing it into a grammatical function, a psychological process which the model presents as composite and stretching out into time.